"Królestwo Boże będzie wam zabrane, a dane narodowi, który wyda jego owoc" (Mt 21, 43) - Kudasiewicz, Józef (The Biblical Annals, 2017)
The paper consists of three parts: 1) an interpretation of Mt 21, 33-46. The „you” („will be taken away from you”) refers to the old Israel. Mattew means here the whole nation (laoV) and not just its leaders; 2) a discussion of the two opposing interpretations of Mt 27, 25: the maximalist one (the whole people is constantly responsible for Jesus’ death; and the minimalist one (Jesus was sentenced not by the people − laoV, but by the crowd − ocloV; 3) an indication that interpretation of Mt 27, 25 requires taking into consideration the Old Testament from which the formula used here is taken. It denotes collective responsibility there. In Jesus’ death Matthew sees the death of an innocent prophet − and not only of just a prophet but of God’s Son. Jesus is a cricial moment in the history of salvation also in the sense that Israel lost its exclusive right to be God’s only people; it is also made up by the former pagans.